2007
DOI: 10.1111/j.1540-8159.2007.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary/Subclavian Vein Puncture Using Navigation by Parallax with an Imaginary Target

Abstract: Navigation by parallax with an imaginary or a real target is effective, easy, and simple, and should facilitate axillary/subclavian vein puncture in multiple clinical scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The record of the original implantation stated the left cephalic vein was not found and central venous access was achieved by direct puncture. The duty physician decided to re-puncture the left axillary-subclavian vein under fluoroscopic guidance [1] but bulked at the first image he saw (Fig. 1).…”
Section: Case Descriptionmentioning
confidence: 99%
“…The record of the original implantation stated the left cephalic vein was not found and central venous access was achieved by direct puncture. The duty physician decided to re-puncture the left axillary-subclavian vein under fluoroscopic guidance [1] but bulked at the first image he saw (Fig. 1).…”
Section: Case Descriptionmentioning
confidence: 99%
“…1,5 Additionally, manipulating multiple leads within the cephalic vein may be difficult and cause lead dislodgement. 15 The technique using ultrasound has obvious advantages because it shows anatomical relationships; however, several factors such as the requirement for special ultrasound equipment, the manipulation technique, or additional manpower could limit its usage. 15, 16 In our study, the simple superficial landmark of the first rib, or occasionally, the radiographic contrast guiding method with axillary venograms was used to access the axillary vein.…”
Section: Kim Kh Et Almentioning
confidence: 99%
“…14 However, this technique may be difficult to apply if the clavicle is caudally displaced with respect to the first rib. 15 Calkins et al showed or manufacturer, the 8-year follow-up result should be a reliable clinical indicator for lead changing when replacing the pacemaker generator. To the best of our knowledge, there has been no report about the relationship between lead fracture/ insulation defect and lead characteristics including structure, insulation material and diameter, and this is the first study to compare lead complication rates over the long term between the subclavian and axillary venous approaches for implantation of permanent pacemakers.…”
Section: Kim Kh Et Almentioning
confidence: 99%
“…The axillary vein is a commonly used extrathoracic access site for cardiac rhythm device lead implantation. A number of studies using fluoroscopic landmarks evaluated the safety and success of the axillary vein puncture . The first rib alone provides a reliable fluoroscopic marker for safe subclavian or axillary vein access without the need for ultrasound guidance or peripheral contrast material administration .…”
mentioning
confidence: 99%